JAMOADA ISH SAMARADORLIGINI OSHIRISH UCHUN MOTIVATSIYA MEXANIZMLARI (Лучшие интеллектуальные исследования, 2025)
Abstract. This article examines the role and importance of motivation mechanisms in improving team performance. It analyzes how to increase employee interest in work, initiative, and overall performance in modern organizations by motivating them. The article examines the theoretical foundations of motivation, as well as practical methods, and highlights the role of management in ensuring effective teamwork. It also provides recommendations on how the correct selection and application of motivational strategies can affect the team environment.